Gendered landscapes of safety: How women construct and navigate the urban landscape to avoid sexual violence - Roberts, Nicola (Criminology & criminal justice, 2022)
This article presents findings from an online survey gathering quantitative and qualitative data from men and women students at a university in the north of England in 2016. The survey explored their perceptions of safety and experiences of interpersonal violence during their time as a student, both on and off campus. We show how women were more likely to report sexual violence compared to men. We also show how women students, compared to men, were less likely to say they never felt unsafe as they moved away from the university into the city, and as they moved from day into night. We illustrate how interconnecting factors construct women’s perceptions of safety, and subsequently, how locations perceived as unsafe ‘hotspots’, become physical barriers impeding women’s access to public and educational spaces. Consequently, we outline measures to enhance women’s safety while at university.